(untitled) (Homoeopathy for All, 2025)
Palliation is temporary relief of symptom of diseases. Palliation is the approach of preventing or treating symptoms and side effects of disease and treatment. Palliation should not only on physical pain but also emotional, social, and spiritual background that arise from illness. It does not depend on the patient’s prognosis and can be provided at any stage of a serious or chronic illness. WHO recognised palliative care as a speciality dedicated exclusively to the relief of suffering and improving the Quality of Life of the patient with life limiting illness. Kerala was the first state to take the initiative and implement a Palliative Care Policy and decided to include homoeopathy in the spectrum of Palliative Care. Homeopathy is capable of bringing the immune system back to its original strength potential. The curability of any condition depends upon the vitality of person to restore the strength of the immune system. If the health a person is more compromised due to long term illness, then less will be the expressions through symptomatology.